2019
DOI: 10.1186/s12864-019-6123-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic analysis of the Hafnia genus reveals an explicit evolutionary relationship between the species alvei and paralvei and provides insights into pathogenicity

Abstract: BackgroundThe Hafnia genus is an opportunistic pathogen that has been implicated in both nosocomial and community-acquired infections. Although Hafnia is fairly often isolated from clinical material, its taxonomy has remained an unsolved riddle, and the involvement and importance of Hafnia in human disease is also uncertain. Here, we used comparative genomic analysis to define the taxonomy of Hafnia, identify species-specific genes that may be the result of ecological and pathogenic specialization, and reveal … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…The genus Hafnia has been reported in Italian ryegrass silage (Heron et al, 1993), but few studies describe it as part of the phyllosphere microbiome of fresh corn. Some Hafnia species are known to be gut pathogens (Yin et al, 2019). Romero et al (2018) and Ni et al (2017) also Downloaded from https://academic.oup.com/jas/article/99/8/skab141/6271125 by UNIVERSITA DEGLI STUDI DI FIRENZE, BIBLIOTECA BIOMEDICA user on 24 February 2022 reported Erwinia and Sphingobacterium in fresh whole-crop corn, but other studies differ in the main genera identified, including Acinetobacter, Klebsiella, and Weissella (Keshri et al, 2018) and Agrobacterium, Microbacterium, and Sphingobacterium (Xu et al, 2019).…”
Section: Phyllosphere Microbial Populationsmentioning
confidence: 99%
“…The genus Hafnia has been reported in Italian ryegrass silage (Heron et al, 1993), but few studies describe it as part of the phyllosphere microbiome of fresh corn. Some Hafnia species are known to be gut pathogens (Yin et al, 2019). Romero et al (2018) and Ni et al (2017) also Downloaded from https://academic.oup.com/jas/article/99/8/skab141/6271125 by UNIVERSITA DEGLI STUDI DI FIRENZE, BIBLIOTECA BIOMEDICA user on 24 February 2022 reported Erwinia and Sphingobacterium in fresh whole-crop corn, but other studies differ in the main genera identified, including Acinetobacter, Klebsiella, and Weissella (Keshri et al, 2018) and Agrobacterium, Microbacterium, and Sphingobacterium (Xu et al, 2019).…”
Section: Phyllosphere Microbial Populationsmentioning
confidence: 99%
“…It is normally isolated from the gastrointestinal tract of animals and humans and from food (Osuka et al, 2011). There are a number of reports on diseases associated with H. alvei and H. paralvei involved in a variety of animal and human infections (Real et al, 1997;Casagrande Proietti et al, 2004;Casanova-Román et al, 2004;Janda and Abbott, 2006;Osuka et al, 2011;Padilla et al, 2013;Orozova et al, 2014;Jayol et al, 2017;Litrenta and Oetgen, 2017;Rodríguez-Alarcón et al, 2019;Yin et al, 2019;Zhang et al, 2019;Cutuli et al, 2021). The main symptoms of H. alvei diseases included hepatosplenomegaly, multifocal nectrotizing hepatitis, and splenitis (Real et al, 1997;Casagrande Proietti et al, 2004;Orozova et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It is almost never associated with antibiotic production except for the antimicrobial activities reported for a strain isolated from the gut of honeybees [ 7 ]. Phylogenetic studies of this little-known species have shown its pan-genome to be open and dynamic with each strain possessing sets of unique genes [ 8 ]. Unique gene acquisition is mainly by horizontal gene transfer, and it reflects the adaptation of strains to their remarkably diverse natural habitats.…”
Section: Objectivementioning
confidence: 99%